Design, analysis, control simulation, and experiment of novel electromagnetic hybrid vibration absorber. (March 2022) - Song, Chunsheng; Xu, Binghui; Fan, Xuefeng; Yang, Pengfei; Duan, Ruirui
This paper presents a novel type of electromagnetic hybrid vibration absorber (EHVA) with a double-ring series permanent magnetic circuit applied to improve the two-stage vibration isolation system of marine power machinery. The EHVA comprises a mover with several groups of coils having a series connection, as well as a stator with internal permanent magnets and external permanent magnets, which form a novel magnetic circuit structure based on an improved Halbach array. In this magnet circuit, two adjacent groups of magnetic induction lines overlap at the coil position, thereby strengthening the magnetic field intensity. When the mover moves axially, the coil cuts the magnetic induction line to produce Lorentz force and magnetic damping force. First, the dynamic parameters of the EHVA were calculated based on multi-rigid-body dynamic theory and fixed-point theory. Second, the mechanical and electromagnetic structures of the EHVA were designed. Finally, a test stand was constructed, the system control channel was identified, and the simulation as well as experiment for vibration control using anH ∞ controller were performed. Results indicated that the hybrid vibration reduction system under control reduced the acceleration amplitude by 12.3 dB at 30.6 Hz and achieved better vibration absorption effects between 27 and 33 Hz compared with the uncontrolled system.